Chemical processes with participation of biological and related compounds : biophysical and chemical aspects of porphyrins, pigments, drugs, biodegradable polymers and nanofibers /: biophysical and chemical aspects of porphyrins, pigments, drugs, biodegradable polymers and nanofibers. (2008) - Unknown
No abstract available